AACR2 to RDA a paradigm shift? - Obille, Kathleen Lourdes B. (2012)
Looks into the history of cataloging and the current change from AACR2 to RDA to determine whether the changes in the past cataloging codes and processes can be considered paradigm shifts. Discusses the changes implemented in some Philippine libraries to accommodate the new cataloging code.
Keywords: Resource description and access; Descriptive Cataloging -- Standards